Students’ Perceived Challenges and Learning Strategies of English Medium of Instruction in the International Nursing Program – A Descriptive Quantitative Study - Komilie Situmorang; Santa Maya Pramusita (STAI Hubbulwathan Duri, 2024)
Achieving international recognition has motivated the universities in Indonesia to shift to international programs. An unmistakable and notable initiative is the adoption of English as the Medium of Instruction (EMI), which has elicited both positive and negative responses. This study investigates the obstacles and educational approaches of nursing students when utilising EMI. The study aims to examine students' perceived problems related to language and learning in an EMI context, as well as the techniques they use. The participants of this study are 176 Indonesian students majoring in Nursing. The participants were asked to fill in the survey questionnaires on the challenges they face and the strategies they use in EMI learning. The collected data were analysed using SPSS quantitatively. The major findings are that most students encountered a moderate level of language and learning challenges and sought L2 support strategies in coping with their language and learning challenges. There is less pressure on the students’ side as no native-speaker teacher is involved in establishing the EMI program. This study concludes that the students are ready for the EMI program. The study further suggests the potential of supporting the students through the concurrent support model by Macaro’s language support model.